Sparking The Impact Of Compensation, Work Motivation, Leadership On Employee Productivity - Saksono, Lalang; Ekasari, Silvia; Nurdiani, Tanti Widia; Tammubua, Milcha Handayani; Marihi, Laode (Yayasan Riset dan Pengembangan Intelektual, 2024)
Research to test the effect of compensation, work motivation, leadership on employee work productivity at PT XYZ in Jakarta. This research uses a quantitative method with multiple linear regression analysis. Data were collected using questionnaires distributed to all employees of PT XYZ in Jakarta. The sampling technique used a census sampling technique with a population of 173 employees. The results of the research show that partially and simultaneously the variables of compensation, work motivation, leadership have a positive and significant effect on employee work productivity at PT XYZ in Jakarta. This finding can be a reference for PT XYZ in Jakarta to increase employee work productivity which has a good impact on organizational performance.